Modeling relationships between water table depth and peat soil carbon loss in Southeast Asian plantations - Kimberly M Carlson; Lael K Goodman; Calen C May-Tobin (Environmental Research Letters, 2015)
Plantation-associated drainage of Southeast Asian peatlands has accelerated in recent years. Draining exposes the upper peat layer to oxygen, leading to elevated decomposition rates and net soil carbon losses. Empirical studies indicate positive relationships between long-term water table (WT) depth and soil carbon loss rate in peatlands. These correlations potentially enable using WT depth as a proxy for soil carbon losses from peatland plantations. Here, we compile data from published research assessing WT depth and carbon balance in tropical plantations on peat. We model net carbon loss from subsidence studies, as well as soil respiration (heterotrophic and total) from closed chamber studies, as a function of WT depth. WT depth across all 12 studies and 59 sites is 67 ± 20 cm (mean ± standard deviation). Mean WT depth is positively related to net carbon loss, as well as soil respiration rate. Our models explain 45% of net carbon loss variation and 45–63% of soil respiration variation. At a 70 cm WT depth, the subsidence model suggests net carbon loss of 20 tC ha ^−1 yr ^−1 (95% confidence interval (CI) 18–22 tC ha ^−1 yr ^−1 ) for plantations drained for >2 yr. Closed chamber-measured total soil respiration at this depth is 20 tC-CO _2 ha ^−1 yr ^−1 (CI 17–24 tC-CO _2 ha ^−1 yr ^−1 ) while heterotrophic respiration is 17 tC-CO _2 ha ^−1 yr ^−1 (CI 14–20 tC-CO _2 ha ^−1 yr ^−1 ), ∼82% of total respiration. While land use is not a significant predictor of soil respiration, WT depths are greater at acacia (75 ± 16 cm) than oil palm (59 ± 15 cm) sample sites. Improved spatio-temporal sampling of the full suite of peat soil carbon fluxes—including fluvial carbon export and organic fertilizer inputs—will clarify multiple mechanisms leading to carbon loss and gain, supporting refined assessments of the global warming potential of peatland drainage.